Development, characterization and evaluation of in vitro safety and in vivo efficacy of repellent gel formulations - da Silva, Márcio Robert Mattos; Castellane, Tereza Cristina Luque [UNESP]; de Sousa, Bruna Fernanda Silva [UNESP]; Lemos, Eliana Gertrudes de Macedo [UNESP]; dos Santos, Elisabete Pereira; Oliveira, Catarina Amorim; Ricci-Junior, Eduardo (Elsevier, 2024)
Contagious diseases caused by mosquito bites are responsible for epidemic outbreaks around the world. Applying mosquito repellents is the main and most cost-effective prophylactic measure to reduce the transmission risk of arboviruses. In this study, two topical gel Formulations were developed as mosquito repellents which use two different systems to release 20 % Icaridin. The first, Formulation 1b uses Pluronic F127®, and the second, Formulation 2b uses a biopolymer produced by bacteria from the Rhizobium tropici species. The repellent Formulations developed showed non-Newtonian behavior. For Formulation 1b the viscosity increased after adding Icaridin. However, for Formulation 2b, there was no increase in viscosity after adding the active substance. The thixotropy analysis showed that the Formulations have good recovery of their structure and adhesion. Adding of Icaridin led to an increase in gel strength in Formulation 1b and did not change the gel strength for Formulation 2b. The Formulations presented very similar occlusion capacities which were all higher than free Icaridin. The Formulations were not cytotoxic in the concentration range between 0.04 % and 0.3 %. In addition, at the 0.62 % concentration, they showed a slight reduction in cell viability, although the LD50 value was not reached. The mean protection time was longer for Formulation 2b compared to Formulation 1b. Both Formulations had a longer mean protection time than free Icaridin against Aedes aegypti. The combination of Icaridin with Pluronic F127® and the biopolymer is an innovation in the pharmaceutical area.